A method for stable and rapid deposition of CVD diamond

By depositing the micro diamond layer, diamond transition layer and nanodiamond layer on the single crystal silicon wafer substrate in sequence, and injecting phosphorus ions into the nanodiamond layer and vacuum annealing treatment, the existing CVD diamond coatings have solved the problems of film layer shedding and insufficient hardness in applications, and the mechanical and electrical performance of diamond composite coatings have been improved, enhancing its application potential in the semiconductor field.

CN116445886BActive Publication Date: 2025-05-02ZHEJIANG HUAMAO TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310291059.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-23
Publication Date
2025-05-02
Estimated Expiration
2043-03-23

AI Technical Summary

Technical Problem

In actual applications, existing CVD diamond coatings have problems such as film layer peeling, insufficient hardness, rough surface, and low conductivity, which are difficult to meet the application needs in the semiconductor field.

Method used

The micro diamond layer, diamond transition layer and nanodiamond layer were deposited on the single crystal silicon wafer substrate by hot wire chemical vapor deposition method in turn, and phosphorus ions were implanted into the nanodiamond layer through ion implantation technology, followed by vacuum annealing to improve the mechanical and electrical properties of the diamond composite coating.

Benefits of technology

It significantly improves the crack propagation resistance, fracture toughness and hardness of diamond composite coatings, reduces the roughness and friction coefficient of the coating, and increases the carrier concentration and mobility, enhancing its application potential in the semiconductor field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004141487380000081
    Figure BDA0004141487380000081
Patent Text Reader

Abstract

The present invention discloses a method for stable and rapid deposition of CVD diamond, wherein a pre-treated single crystal silicon wafer is used as a substrate, a micron diamond layer, a diamond transition layer and a nano diamond layer are sequentially deposited on one side of the substrate by hot wire chemical vapor deposition, and then donor impurity ions are injected into the nano diamond layer by ion implantation, and vacuum annealing, cleaning and drying are performed to obtain the diamond layer. The present invention complements the advantages of each layer, reduces internal stress, improves the bonding strength between the coating and the substrate, and between the coatings, and thus improves the mechanical properties of the diamond composite coating through material selection, structural optimization and process control; impurity elements are introduced into the diamond coating, and the mechanical properties and deposition speed of the material are increased while minimizing the diamond lattice distortion, and the coating has a higher Hall mobility and carrier concentration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of diamonds, and in particular relates to a method for stably and rapidly depositing CVD diamonds. Background Art

[0002] Diamond has attracted everyone's attention due to its extremely excellent physical and chemical properties. However, the reserves of natural diamonds are limited, so people have developed a variety of methods for artificial diamond synthesis, such as high temperature and high pressure method (HPHT), hot wire chemical vapor deposition method (HJCVD), and microwave plasma chemical vapor deposition method (MPCVD). Chemical vapor deposition (CVD) diamond coating has many excellent properties close to natural diamonds, such as high hardness, high wear resistance, high thermal conductivity, low friction coefficient and good chemical inertness. Depositing diamond coating on the surface of widely used cemented carbide tools can greatly increase the service life of the tools, improve cutting conditions, and improve the processing quality of workpieces.

[0003] The patent application number 201810246649.X provides a high-mobility n-type ultra-thin nanodiamond film and its preparation method. The patent first deposits an AlN transition layer on a high-resistance silicon substrate by physical vapor deposition, and then prepares an ultra-thin nanodiamond film on the AlN transition layer by hot wire chemical vapor deposition. The diamond film provided by the patent has a small content of grain boundaries, and the injected oxygen, phosphorus, and sulfur ions are concentrated inside the nanodiamond particles instead of in the grain boundaries, which is conducive to improving the n-type conductivity of the film. Its mobility can reach 522, 401, and 119 cm at room temperature, respectively. 2 / (V·s), but compared with micron diamond film, nano diamond film has lower hardness and film-base adhesion strength, and the film layer is prone to fall off in practical applications. CVD diamond coatings are divided into micron diamond coatings and nano diamond coatings. Micron diamond film has high crystallinity, good adhesion to the substrate, high hardness, better wear resistance, and can effectively improve the service life of the coating. However, due to the coarse grains, the surface of micron diamond film is rough, which has a significant impact on the processing quality of products in the fields of cutting, mold drawing, etc. The high hardness of the micron film also makes its surface finishing more time-consuming and labor-intensive. In addition, its coating toughness and crack growth resistance are also poor; nano diamond film has good surface smoothness, which can significantly reduce cutting force and heat, improve cutting conditions, and the nano diamond coating with continuous growth structure also has good crack growth resistance, but the bonding strength between the coating and the substrate is low. The patent with application number 201810127560.1 provides a low-stress CVD diamond composite coating and a preparation method thereof. The specific steps are: on the surface of the pretreated cemented carbide substrate, a time modal method is used to alternately deposit a micron diamond coating and a nano diamond coating by hot wire CVD, wherein the micron diamond is a cyclic deposition process of "thin film growth-hydrogen reduction", and the nano diamond is a cyclic deposition process of "thin film growth-argon etching, hydrogen reduction". This patent uses the time modal method to release and reduce thermal stress during the deposition of the diamond coating, thereby improving the bonding strength between the coating and the substrate and the composite coating. However, the diamond coating has low electrical conductivity and low electron mobility, making it difficult to use as an electronic device, which seriously hinders its application in the semiconductor field.

[0004] Therefore, the key to developing diamond technology lies not only in the use of composite coating technology, taking advantage of the complementary performance advantages of micron diamond coating and nano diamond coating to enhance the mechanical properties of diamond composite coating such as crack propagation resistance, fracture toughness and hardness, but also in the use of co-doping, ion implantation and other methods to enhance the electrical properties of diamond coating such as carrier concentration and mobility while minimizing diamond lattice distortion. Summary of the invention

[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide a method for stably and rapidly depositing CVD diamond.

[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:

[0007] A method for stably and rapidly depositing CVD diamond, using a pre-treated single crystal silicon wafer as a substrate, using a hot wire chemical vapor deposition method to sequentially deposit a micron diamond layer, a diamond transition layer and a nano diamond layer on one side of the substrate, then using an ion implantation method to implant donor impurity ions into the nano diamond layer, and vacuum annealing, cleaning and drying to obtain CVD diamond.

[0008] The above method for stable and rapid deposition of CVD diamond specifically comprises the following steps:

[0009] S1. Pretreatment: grinding, cleaning and drying the single crystal silicon wafer to obtain a substrate;

[0010] S2, depositing a micron diamond layer: using a mixed gas of acetone, hydrogen, argon, a boron source, and a silicon source as a growth gas source, depositing a micron diamond layer on the surface of the substrate obtained in step S1, wherein the substrate temperature is 700-750°C, the reaction pressure is 800-1200Pa, the deposition time is 1.5-2.5h, the total flow rate of the growth gas source is 450-600sccm, and the volume of argon accounts for 26-29% of the total volume of the growth gas source;

[0011] S3, depositing a diamond transition layer: using a mixed gas of acetone, hydrogen, argon and nitrogen source as a growth gas source, depositing a diamond transition layer on the surface of the micron diamond layer, wherein the substrate temperature is 720-770°C, the reaction pressure is 800-1200Pa, the deposition time is 1-1.5h, the total flow rate of the growth gas source is 450-600sccm, and the volume of argon accounts for 31-34% of the total volume of the growth gas source;

[0012] S4, depositing a nano-diamond layer: using a mixed gas of acetone, hydrogen and argon as a growth gas source, depositing a nano-diamond layer on the surface of the diamond transition layer, wherein the substrate temperature is 750-800°C, the reaction pressure is 800-1200Pa, the deposition time is 0.5-1h, the total flow rate of the growth gas source is 450-600sccm, and the volume of argon accounts for 36-39% of the total volume of the growth gas source;

[0013] S5. Phosphorus ion implantation: Phosphorus ions are implanted into the nano-diamond layer using an ion implantation method. The phosphorus ion implantation dose is 10 10 -10 14 cm -2 , the injection energy is 55-85keV;

[0014] S6, vacuum annealing treatment: placing the product obtained in step S5 in a vacuum heating furnace, adjusting the vacuum degree to 3000-7000 Pa, annealing at a temperature of 900-1100° C. for 30-50 min, stopping heating, and cooling to room temperature with the furnace;

[0015] S7, cleaning and drying: The surface of the product obtained in step S6 is first cleaned with acetone, then cleaned with a mixed solution of 75% sulfuric acid and hydrogen peroxide for 5-10 minutes, and dried with nitrogen to obtain CVD diamond.

[0016] The present invention adopts hot wire chemical vapor deposition technology, and realizes the transformation of the diamond film morphology from micron grains to nano grains by controlling the deposition process parameters. A micron diamond layer, a diamond transition layer and a nano diamond layer are sequentially deposited on a pretreated substrate. The grain size is sequentially reduced during the deposition process, which can reduce internal stress and improve the bonding strength between the coating and the substrate and between the coatings. There are differences in the properties of the micron diamond layer and the nano diamond layer. A diamond transition layer is arranged between the two layers, so that the advantages of each layer are complementary, and the mechanical properties of the diamond composite coating such as crack propagation resistance, fracture toughness and hardness are significantly improved, while the roughness and friction coefficient of the coating surface are effectively reduced. When depositing the micron diamond layer, a boron source gas and a silicon source gas are introduced into the gas phase system, so that boron and silicon elements are uniformly and stably doped into the diamond coating, and the boron element and the silicon element form a synergistic effect, thereby improving the crystal phase change. The reversibility and stability of the crystal structure can be improved, the internal stress can be reduced, the mechanical properties of the material can be increased, and the electrical properties such as the carrier concentration and mobility of the diamond coating can be improved; doping nitrogen in the diamond transition layer can increase the film deposition rate, reduce the internal stress, increase the wear resistance and hardness, etc., and at the same time make the micron grains and nano grains more closely combined, and improve the interlayer adhesion; a certain amount of phosphorus ions are simultaneously doped into the grains and grain boundaries of the nano diamond layer by ion implantation, so that the coating has a higher Hall mobility and carrier concentration; vacuum annealing of the diamond composite coating can reduce the effect of element doping on the diamond lattice distortion, restore the lattice integrity of the diamond grains, reduce the internal stress, and promote the transformation of part of the amorphous carbon into the diamond phase, providing an opportunity for the doping elements to diffuse into the diamond grains, and improving the mechanical and electrical properties of the diamond coating.

[0017] In order to add defects and dangling bonds on the substrate and increase the nucleation rate and nucleation density during the deposition of the diamond film, the specific steps of the pretreatment in step S1 are: grinding the single crystal silicon wafer with a micron-grade diamond grinding paste for 30-40 minutes, then soaking it in a hydrofluoric acid solution with a concentration of 20-25% for 15-20 minutes, and then ultrasonically cleaning it in acetone and ethanol solutions for 10-15 minutes respectively, and blowing it dry with nitrogen.

[0018] In order to control the diamond grain size and lattice distortion, improve the carrier concentration, electron mobility, hardness and fracture toughness of the diamond film, and reduce the internal stress, the deposition in steps S2, S3 and S4 adopts hot wire chemical vapor deposition, the hot wire power is 1700-2200W, the acetone is introduced into the reaction chamber by hydrogen bubbling, the flow ratio of hydrogen to acetone during the hydrogen bubbling process is 20:5-8, the acetone flow rate is 15-40sccm, the boron source in step S2 is trimethylborane, and the boron source enters the reaction chamber by a mixed boron-doped gas composed of trimethylborane and hydrogen, and the introduction flow rate of the mixed boron-doped gas is 40-160scc m, the volume fraction of trimethylborane in the mixed boron-doped gas is 0.5-1%, the silicon source is monosilane, the silicon source enters the reaction chamber by introducing a mixed silicon-doped gas composed of monosilane and hydrogen, the introduction flow rate of the mixed silicon-doped gas is 50-120 sccm, and the volume fraction of monosilane in the mixed silicon-doped gas is 1-2%, the nitrogen source in step S3 is nitrogen, the nitrogen source enters the reaction chamber by introducing a mixed nitrogen-doped gas composed of nitrogen and hydrogen, the introduction flow rate of the mixed nitrogen-doped gas is 50-70 sccm, and the volume fraction of nitrogen in the mixed nitrogen-doped gas is 6-8%, and the volume ratio of 75% sulfuric acid to hydrogen peroxide in step S7 is 1:1-1.2.

[0019] The invention has the following beneficial effects: the invention controls the grain size of diamond by adjusting the process parameters of hot wire chemical vapor deposition, so that the grain size of diamond is reduced in sequence during the deposition process, internal stress is reduced, the bonding strength between the coating and the substrate and between the coatings is improved, and the mechanical properties such as crack propagation resistance, fracture toughness and hardness of the diamond composite coating are significantly improved; high temperature and low pressure heat treatment can also improve the fracture toughness of the diamond film without losing the hardness of the diamond; boron silicon co-doping and phosphorus ion implantation improve the reversibility of the diamond crystal phase change and the stability of the crystal structure, and increase the mechanical properties of the material. The mechanical properties of the coating are improved, and the coating has a higher Hall mobility and carrier concentration. The introduction of nitrogen can increase the coating deposition speed, increase wear resistance, hardness, etc., and make the micron grains and nano grains more closely combined, and improve the interlayer adhesion; vacuum annealing of the diamond composite coating can reduce the influence of element doping on the diamond lattice distortion, restore the lattice integrity of the diamond grains, reduce internal stress, and promote the transformation of part of the amorphous carbon into the diamond phase, providing an opportunity for the doping elements to diffuse into the diamond grains, and further improve the mechanical properties and electrical properties of the diamond coating. The CVD diamond provided by the present invention has the characteristics of fast and stable deposition process, high carrier concentration, high mobility, high fracture toughness, etc. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0021] Example 1

[0022] A method for stably and rapidly depositing CVD diamond comprises the following steps:

[0023] S1, pretreatment: grinding a single crystal (111) silicon wafer with a micron-grade diamond grinding paste (2 μm, purchased from Dongguan Henkel Industrial Co., Ltd.) for 30 min, then soaking it in a 25% hydrofluoric acid solution for 15 min, then ultrasonically cleaning it in acetone and ethanol solutions for 15 min, and drying it with nitrogen to obtain a substrate;

[0024] S2, depositing a micron diamond layer: using a mixed gas of acetone, hydrogen, argon, a boron source and a silicon source as a growth gas source, depositing a micron diamond layer on the surface of the substrate obtained in step S1, wherein the substrate temperature is 720°C, the reaction pressure is 1000Pa, the deposition time is 2h, the total flow rate of the growth gas source is 500sccm, the volume of argon accounts for 27.5% of the total volume of the growth gas source (the argon flow rate is 137.5sccm), the deposition adopts a hot wire chemical vapor deposition method, and the hot wire power is 1800W; the thickness of the micron diamond layer is 2950-3050nm;

[0025] Among them, the gases entering the reaction chamber are:

[0026] ① Hydrogen containing acetone (i.e., acetone enters the reaction chamber by hydrogen bubbling), with an inflow rate of 52.5 sccm (the flow ratio of hydrogen to acetone during hydrogen bubbling is 20:8, the acetone flow rate is 15 sccm, and the hydrogen flow rate during hydrogen bubbling is 37.5 sccm);

[0027] ② mixed boron-doped gas (i.e., the boron source is trimethylborane, and a mixed boron-doped gas consisting of trimethylborane and hydrogen is introduced), with an introduction flow rate of 100 sccm (the volume fraction of trimethylborane in the mixed boron-doped gas is 1%, and when the mixed boron-doped gas is introduced, the hydrogen flow rate is 99 sccm, and the trimethylborane flow rate is 1 sccm);

[0028] ③ Mixed silicon-doped gas (i.e., the silicon source is monosilane, and a mixed silicon-doped gas consisting of monosilane and hydrogen is introduced), with an introduction flow rate of 100 sccm (the volume fraction of monosilane in the mixed silicon-doped gas is 2%, and when the mixed silicon-doped gas is introduced, the hydrogen flow rate is 98 sccm, and the monosilane flow rate is 2 sccm);

[0029] ③ Hydrogen, with an inlet flow rate of 110 sccm;

[0030] ④ Argon, flow rate is 137.5sccm;

[0031] S3. Deposition of diamond transition layer: Using a mixed gas of acetone, hydrogen, argon and nitrogen source as the growth gas source, a diamond transition layer is deposited on the surface of the micron diamond layer, wherein the substrate temperature is 750°C, the reaction pressure is 1000Pa, the deposition time is 1h, the total flow rate of the growth gas source is 500sccm, the volume of argon accounts for 32.5% of the total volume of the growth gas source (the argon flow rate is 162.5sccm), the flow rate of hydrogen introduced alone is 235sccm, the deposition adopts hot wire chemical vapor deposition method, the hot wire power is 2000W, and the acetone is bubbled with hydrogen The method comprises the following steps: the flow rate ratio of hydrogen to acetone during hydrogen bubbling is 20:8, the flow rate of acetone is 15 sccm, the flow rate of hydrogen during hydrogen bubbling is 37.5 sccm, the nitrogen source is nitrogen, a mixed nitrogen-doped gas composed of nitrogen and hydrogen is introduced, the flow rate of the mixed nitrogen-doped gas is 50 sccm, the volume fraction of nitrogen in the mixed nitrogen-doped gas of nitrogen and hydrogen is 7%, the flow rate of hydrogen when the mixed nitrogen-doped gas is introduced is 46.5 sccm, the flow rate of nitrogen is 3.5 sccm, and the thickness of the diamond transition layer is 800-870 nm;

[0032] S4, deposition of nano-diamond layer: using a mixed gas of acetone, hydrogen and argon as a growth gas source, a nano-diamond layer is deposited on the surface of the diamond transition layer, wherein the substrate temperature is 780°C, the reaction pressure is 1000Pa, the deposition time is 0.5h, the total flow rate of the growth gas source is 500sccm, the volume of argon accounts for 37.5% of the total volume of the growth gas source (the argon flow rate is 187.5sccm), the flow rate of hydrogen introduced alone is 260sccm, the deposition adopts hot wire chemical vapor deposition method, the hot wire power is 2200W, acetone is introduced into the reaction chamber by hydrogen bubbling, the flow ratio of hydrogen to acetone during the hydrogen bubbling process is 20:8, the acetone flow rate is 15sccm, the hydrogen flow rate during the hydrogen bubbling process is 37.5sccm, and the thickness of the nano-diamond layer is 200-240nm;

[0033] S5. Phosphorus ion implantation: Phosphorus ions are implanted into the nano-diamond layer using an ion implantation method. The phosphorus ion implantation dose is 10 12 cm -2 , the injection energy is 60keV;

[0034] S6, vacuum annealing treatment: placing the product obtained in step S5 in a vacuum heating furnace, adjusting the vacuum degree to 6000 Pa, annealing at a temperature of 1000° C. for 30 min, stopping heating, and cooling to room temperature with the furnace;

[0035] S7, cleaning and drying: The surface of the product obtained in step S6 is first cleaned with acetone, then cleaned with a mixed solution of 75% sulfuric acid and hydrogen peroxide for 5 minutes, and blown dry with nitrogen to obtain CVD diamond, wherein the volume ratio of 75% sulfuric acid to hydrogen peroxide is 1:1.

[0036] According to the micron diamond layer deposition process and nano diamond layer deposition process provided in this embodiment, a single-layer micron diamond film and a single-layer nano diamond film of the same thickness were prepared respectively, and the surface roughness was measured by a surface profilometer. The results showed that the roughness of the CVD diamond film provided in this embodiment was 300nm lower than that of the single-layer micron diamond film, which was equivalent to the roughness of the single-layer nano diamond film. The friction coefficient was measured by a reciprocating friction tester. The results showed that the average friction coefficient of the CVD diamond film provided in this embodiment was 65% lower than that of the single-layer micron diamond film, which was close to the friction coefficient value of the single-layer nano diamond film, indicating that the CVD diamond film provided in this embodiment has tribological properties close to those of the single-layer nano diamond film.

[0037] Example 2

[0038] A method for stably and rapidly depositing CVD diamond is prepared according to the method of Example 1, except that the deposition times in steps S2, S3 and S4 are 2.5 h, 1.5 h and 1 h respectively.

[0039] Example 3

[0040] A method for stably and rapidly depositing CVD diamond is prepared according to the method of Example 1, except that the volume of argon gas in steps S2, S3 and S4 accounts for 26%, 31% and 36% of the total volume of the gas, respectively.

[0041] Example 4

[0042] A method for stably and rapidly depositing CVD diamond is prepared according to the method of Example 1, except that the volume of argon gas in steps S2, S3 and S4 accounts for 29%, 34% and 39% of the total volume of the gas, respectively.

[0043] Example 5

[0044] A method for stably and rapidly depositing CVD diamond is prepared according to the method of Example 1, except that the annealing temperature in step S6 is 900°C.

[0045] Example 6

[0046] A method for stably and rapidly depositing CVD diamond is prepared according to the method of Example 1, except that the annealing temperature in step S6 is 1100°C.

[0047] Comparative Example 1

[0048] A method for stably and rapidly depositing CVD diamond is prepared according to the method of Example 1, except that step S3 is omitted.

[0049] Comparative Example 2

[0050] A method for stably and rapidly depositing CVD diamond is prepared according to the method of Example 1, except that the reaction pressure in steps S2, S3 and S4 is 1500 Pa.

[0051] Comparative Example 3

[0052] A method for stably and rapidly depositing CVD diamond is prepared according to the method of Example 1, except that step S6 is omitted.

[0053] The CVD diamonds prepared in Examples 1-6 and Comparative Examples 1-3 were subjected to relevant performance tests, wherein the electrical performance test was measured using the Accent HL5500 Hall system at room temperature using the Van der Pauw method; the hardness and fracture toughness tests were measured using the Vickers hardness test method with a test load of 1 kg. The results are shown in Table 1.

[0054] Table 1 Diamond performance test results

[0055]

[0056] It can be seen from Table 1 that the carrier concentration, mobility and fracture toughness of the CVD diamonds prepared in Examples 1-6 are better than those in Comparative Examples 1-3, and the comprehensive performance of the CVD diamond prepared in Example 1 is the best; compared with Examples 2-6 and Comparative Example 2, the deposition time, the percentage of argon volume in the total gas volume, the vacuum annealing temperature and the reaction pressure in Example 1 can all affect the carrier concentration, mobility, hardness and fracture toughness of the CVD diamond, which may be related to the diamond grain size, lattice distortion degree, diamond film purity, etc.; compared with Comparative Example 1, in Example 1, a diamond transition layer is deposited between the micron diamond layer and the nano diamond layer, which can improve the carrier concentration and mobility of the CVD diamond to a certain extent, and can significantly improve the fracture toughness of the CVD diamond; compared with Comparative Example 3, in Example 1, after vacuum annealing at 1000° C., the hardness of the CVD diamond is slightly reduced, but the carrier concentration, mobility and fracture toughness are greatly improved.

[0057] The present invention controls the process parameters of hot wire chemical vapor deposition to sequentially deposit a micron diamond layer, a diamond transition layer and a nano diamond layer on a pretreated substrate, so that the advantages of each layer are complementary, internal stress is reduced, and the bonding strength between the coating and the substrate and between the coatings is improved, thereby improving the mechanical properties of the diamond composite coating; impurity elements are introduced into the diamond coating to increase the mechanical properties and deposition speed of the material, and to enable the coating to have a higher Hall mobility and carrier concentration; a vacuum annealing method is adopted to enhance the electrical properties of the diamond coating, such as the carrier concentration and mobility, while minimizing the diamond lattice distortion.

[0058] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A method for stable and rapid deposition of CVD diamond, characterized in that: Using a pre-treated single crystal silicon wafer as a substrate, a micron diamond layer, a diamond transition layer and a nano diamond layer are sequentially deposited on one side of the substrate by hot wire chemical vapor deposition, and then donor impurity ions are implanted into the nano diamond layer by ion implantation. After vacuum annealing, cleaning and drying, CVD diamond is obtained. The following steps are involved: S1. Pretreatment: grinding, cleaning and drying the single crystal silicon wafer to obtain a substrate; S2, depositing a micron diamond layer: using a mixed gas of acetone, hydrogen, argon, a boron source, and a silicon source as a growth gas source, depositing a micron diamond layer on the surface of the substrate obtained in step S1, wherein the substrate temperature is 700-750°C, the reaction pressure is 800-1200Pa, the deposition time is 1.5-2.5h, the total flow rate of the growth gas source is 450-600sccm, and the volume of argon accounts for 26-29% of the total volume of the growth gas source; S3, depositing a diamond transition layer: using a mixed gas of acetone, hydrogen, argon and nitrogen source as a growth gas source, depositing a diamond transition layer on the surface of the micron diamond layer, wherein the substrate temperature is 720-770°C, the reaction pressure is 800-1200Pa, the deposition time is 1-1.5h, the total flow rate of the growth gas source is 450-600sccm, and the volume of argon accounts for 31-34% of the total volume of the growth gas source; S4, depositing a nano-diamond layer: using a mixed gas of acetone, hydrogen and argon as a growth gas source, depositing a nano-diamond layer on the surface of the diamond transition layer, wherein the substrate temperature is 750-800°C, the reaction pressure is 800-1200Pa, the deposition time is 0.5-1h, the total flow rate of the growth gas source is 450-600sccm, and the volume of argon accounts for 36-39% of the total volume of the growth gas source; S5. Phosphorus ion implantation: Phosphorus ions are implanted into the nano-diamond layer using an ion implantation method. The phosphorus ion implantation dose is 10 10 -10 14 cm -2 , the injection energy is 55-85keV; S6, vacuum annealing treatment: placing the product obtained in step S5 in a vacuum heating furnace, adjusting the vacuum degree to 3000-7000 Pa, annealing at a temperature of 900-1100° C. for 30-50 min, stopping heating, and cooling to room temperature with the furnace; S7, cleaning and drying: The surface of the product obtained in step S6 is first cleaned with acetone, then cleaned with a mixed solution of 75% sulfuric acid and hydrogen peroxide for 5-10 minutes, and dried with nitrogen to obtain CVD diamond; The specific steps of the pretreatment in step S1 are: grinding the single crystal silicon wafer with micron-grade diamond grinding paste for 30-40 minutes, then soaking it in a hydrofluoric acid solution with a concentration of 20-25% for 15-20 minutes, then ultrasonically cleaning it in acetone and ethanol solutions for 10-15 minutes respectively, and drying it with nitrogen gas to obtain; The deposition in steps S2, S3 and S4 all adopts hot wire chemical vapor deposition method, the hot wire power is 1700-2200W, the acetone is introduced into the reaction chamber by hydrogen bubbling, the flow ratio of hydrogen to acetone during hydrogen bubbling is 20:5-8, and the acetone flow rate is 15-40sccm; Among them, boron silicon co-doping and phosphorus ion implantation improve the reversibility of diamond crystal phase transition and the stability of crystal structure.

2. A method for stable and rapid deposition of CVD diamond according to claim 1, characterized in that: The boron source in step S2 is trimethylborane, and the boron source enters the reaction chamber by introducing a mixed boron-doped gas composed of trimethylborane and hydrogen. The introduction flow rate of the mixed boron-doped gas is 40-160 sccm, and the volume fraction of trimethylborane in the mixed boron-doped gas is 0.5-1%.

3. The method for stable and rapid deposition of CVD diamond according to claim 1, characterized in that: The silicon source in step S2 is monosilane, and the silicon source enters the reaction chamber by introducing a mixed silicon-doped gas composed of monosilane and hydrogen. The introduction flow rate of the mixed silicon-doped gas is 50-120 sccm, and the volume fraction of monosilane in the mixed silicon-doped gas is 1-2%.

4. The method for stable and rapid deposition of CVD diamond according to claim 1, characterized in that: The nitrogen source in step S3 is nitrogen. The nitrogen source enters the reaction chamber by introducing a mixed nitrogen-doped gas composed of nitrogen and hydrogen. The introduction flow rate of the mixed nitrogen-doped gas is 50-70 sccm, and the volume fraction of nitrogen in the mixed nitrogen-doped gas is 6-8%.

5. The method for stable and rapid deposition of CVD diamond according to claim 1, characterized in that: The volume ratio of 75% sulfuric acid to hydrogen peroxide in step S7 is 1:1-1.2.

Citation Information

Patent Citations

  • Low-stress chemical vapor deposition (CVD) diamond composite coating and preparation method thereof

    CN108385085A

  • Method for preparing diamond film through multiple-doped hot filament chemical vapor deposition

    CN102586762A

  • High-mobility n-type ultrathin nano diamond film and preparation method thereof

    CN108531883A

  • Method for preparing thickness controllable trilayer type diamond membrane

    CN1928151A